Strategi Pemasaran Pembiayaan Kepemilikan Rumah pada Bank SUMUT KCP SY HM YAMIN - Muhammad Rijal Fanshury Hasibuan; Nurul Jannah (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study was to obtain a marketing strategy for KPR products of Bank Sumut Syariah for Bank Sumut Syariah KCP SY HM Yamin in increasing bank income. This research is a type of descriptive research using a qualitative approach. Information obtained from interviews, field identification, literature review sourced from journals and critical thinking from the author. By doing a SWOT analysis of FLPP mortgage financing at Bank Sumut KCP Sy HM Yamin, the results of the Cartesian diagram show the company's position is in quadrant I (growth), which is a very profitable situation for the company. So, Bank Sumut KCP Sy HM Yamin still has the strength to take advantage of existing opportunities as well as possible in order to minimize weaknesses and overcome threats. The strategy applied in this condition is to support an aggressive growth policy (Growth Oriented Strategy, namely by doing agile growth, the company takes advantage of prime conditions to continue to increase expansion, growth and maximize opportunities